Degradation of Kapok Fiber-Reinforced Polyester Composites with Calcium Carbonate Filler in Seawater - Suprayadi, Lalu Nata; b, Jauhar Fajrin (International Journal of Membrane Science and Technology, 2023)
This research investigates the development of polyester composites reinforced with kapok fiber and CaCO3 filler to reduce environmental impact. Natural fibers, valued for their lightweight, fire resistance, cost-effectiveness, and biodegradability, are commonly used in composites. However, synthetic fibers, despite their superior mechanical properties, raise environmental concerns. The study focuses on the composites’ performance, stability, and endurance in harsh conditions. Kapok fibers were manually extracted, and CaCO3 powder was sieved to 80 mesh. Composite samples were created with varying volume fractions of CaCO3 powder and kapok fibers, using polyester as the matrix. Tensile and bending tests, according to ASTM D3039 and ASTM D790 standards, were conducted on these samples. Additionally, water absorption was assessed gravimetrically, and mechanical strength degradation was studied via immersion in artificial seawater at different temperatures. Results indicated that water absorption increased with higher fiber volume fractions in the composite, primarily due to the water-absorbing capabilities of natural fibers and CaCO3 particles, surpassing that of polyester resin. Increased immersion temperatures accelerated water diffusion, impacting interactions between water molecules, polymer chains, and natural fibers. Furthermore, an increase in the CaCO3 filler volume fraction negatively affected the mechanical strength of kapok polyester-fiber composites. This was attributed to the agglomeration of CaCO3 powder, disrupting the polyester resin’s viscosity and damaging the bond between kapok fiber and the matrix. The composites exhibited their highest tensile strength with 10% CaCO3 filler before immersion, but this strength decreased following exposure to high temperatures.